2016
DOI: 10.1158/0008-5472.can-15-3130
|View full text |Cite
|
Sign up to set email alerts
|

CD27 Agonism Plus PD-1 Blockade Recapitulates CD4+ T-cell Help in Therapeutic Anticancer Vaccination

Abstract: While showing promise, vaccination strategies to treat cancer require further optimization. Likely barriers to efficacy involve cancer-associated immunosuppression and peripheral tolerance, which limit the generation of effective vaccine-specific cytotoxic T lymphocytes (CTL

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
110
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 47 publications
9
110
1
1
Order By: Relevance
“…Recent studies have demonstrated that CD27 engagement can lead to Fas expression and T cell apoptosis, while other studies have seen an increased in the expression of the immune checkpoint PD-1. 42,43 In support of these observations, our supplemental Figure 4 demonstrates that administration of αhCD27 with vaccination increases the expression of PD-1 on CD8 + T cells. Importantly, a recent study showed that PD-1 blockade can augment the efficacy of αhCD27 administration in the absence of vaccination through increasing T cell cytotoxicity.…”
Section: Discussionsupporting
confidence: 63%
“…Recent studies have demonstrated that CD27 engagement can lead to Fas expression and T cell apoptosis, while other studies have seen an increased in the expression of the immune checkpoint PD-1. 42,43 In support of these observations, our supplemental Figure 4 demonstrates that administration of αhCD27 with vaccination increases the expression of PD-1 on CD8 + T cells. Importantly, a recent study showed that PD-1 blockade can augment the efficacy of αhCD27 administration in the absence of vaccination through increasing T cell cytotoxicity.…”
Section: Discussionsupporting
confidence: 63%
“…CD27 signaling is controlled by its ligand, CD70, the expression of which is transient upon activation of dendritic cells (DCs), B cells, and T cells, and is tightly regulated (11)(12)(13). CD70-CD27 interaction provides a potent second signal for CD4 T cell-dependent and -independent CD8 T cell priming, effector differentiation, and memory development in virus clearance or tumor rejection (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Human CD27 or CD70 deficiency due to genetic mutations resulted in persistent symptomatic EBV infection and EBV-associated lymphoproliferative disorders, including lethal lymphoma (26)(27)(28)(29)(30).…”
mentioning
confidence: 99%
“…This conclusion was also made in one recent study using the TC-1 tumor model and vaccination with conventional DNA encoding E7sh. 35 The authors achieved 100% survival by combining vaccination with CD27 agonism and programmed death receptor 1 (PD1) blockade. 35 At day 15 after tumor inoculation, the combined treatments resulted in approximately 20% of E7-specific T cells compared to 60% with replacing PD1 blockade with cytotoxic T-lymphocyte-associated protein 4 (CTLA-4).…”
Section: Discussionmentioning
confidence: 99%
“…35 The authors achieved 100% survival by combining vaccination with CD27 agonism and programmed death receptor 1 (PD1) blockade. 35 At day 15 after tumor inoculation, the combined treatments resulted in approximately 20% of E7-specific T cells compared to 60% with replacing PD1 blockade with cytotoxic T-lymphocyte-associated protein 4 (CTLA-4). However, CTLA-4 blockade with CD27 agonism and vaccination resulted in half of mice surviving by day 100.…”
Section: Discussionmentioning
confidence: 99%